2021
DOI: 10.1039/d1ta05058c
|View full text |Cite
|
Sign up to set email alerts
|

MXene aerogel for efficient photothermally driven membrane distillation with dual-mode antimicrobial capability

Abstract: Solar-driven desalination, which involves the conversion of solar energy to heat for freshwater generation, has been recognized as an attractive and sustainable desalination technology to alleviate freshwater shortage. In particular,...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(14 citation statements)
references
References 73 publications
0
13
0
Order By: Relevance
“…[144] To retard the spontaneous oxidation of MXene, Cao et al prepared an intriguing example of air-stable tridecafluoro-1,1,2,2tetrahydrooctyl-trichlorosilane (FTCS)-treated MXene/ PVA/hydroxyapatite (HA) composite aerogels. [145] The FTCS and d) the corresponding distribution of the normalized current change on the sensing array. Reproduced with permission.…”
Section: Solar Steam Generatormentioning
confidence: 99%
“…[144] To retard the spontaneous oxidation of MXene, Cao et al prepared an intriguing example of air-stable tridecafluoro-1,1,2,2tetrahydrooctyl-trichlorosilane (FTCS)-treated MXene/ PVA/hydroxyapatite (HA) composite aerogels. [145] The FTCS and d) the corresponding distribution of the normalized current change on the sensing array. Reproduced with permission.…”
Section: Solar Steam Generatormentioning
confidence: 99%
“…The use of the solar-driven thermal distillation technique to generate clean water from salt, brine, and contaminated water can be traced back to a very early stage in human history until now. [6][7][8][9][10][11][12][13][14][15][16] However, only water itself typically exhibits low evaporation rates in the range of 0.2-0.5 kg m À2 h À1 partly due to low energy conversion (<50%) under one sun irradiation. [17][18][19][20][21] As such, devices with better photothermal conversion ability, or solar evaporators, have been developed to improve the rate of evaporation and energy conversion efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…Besides the abiotic pollutants, biofouling induced by microorganisms is another critical constraint for the durability of water treatment materials and plants. 27,28 Our previous investigation has showed that biomimetic aerogels with the anti-biofouling design could prevent a sharp decrease in water evaporation rates by inhibiting the clogging of pores. 29 Despite prokaryotic microbes, natural water was also occupied by numerous eukaryotic microbes such as fungus, which equally account for the formation of biofilms on water purifiers.…”
Section: Introductionmentioning
confidence: 99%